The Analysis of Errors on Translating Informative Texts by Google Translate - Ismailia, Titik (JETLEE : Journal of English Language Teaching, Linguistics, and Literature, 2022)
This research aims to describe and classify the errors that was made by students in translating informative text in English into “Bahasa Indonesia” with Google translate (GT) application. This research applies errors analysis method with content analysis approach. The procedure to do the research are: data collection, identification of errors, classification of errors, and statement of errors frequency. The result shows that the errors mostly found in lexis level such as omission, adding, and untranslated both in content and function. While in the grammar level, there were some errors found like the word class changing, tenses, and agreement. In semantic level, there were errors on confusion of senses, wrong choice, and idioms. Lastly, in discourse level there were errors on style, variety, and should not be translated. To conclude, the lexical errors that found in the result of translating informative text by Google is for about 98 %. The other errors also found in grammar for about 0,007%, semantic for about 0.008% and discourse for about 0.005%. It means that Google translate made many errors in translating informative text, but it can be as an alternative choice to get the rapid translation result from English text into Bahasa Indonesia.